Validation of Genetic Variants Associated with Early Acute Rejection in Kidney Allograft Transplantation - Oetting, William S. (2011)
Numerous reports have identified genetic variants associated with kidney transplant outcome; but only a few have been validated in subsequent studies. We analyzed the association of 21 previously reported genetic variants associated with acute rejection (AR), in an effort to validate these associations in our kidney transplant population. All recipients (n=585) received Ab induction, rapid discontinuation of prednisone, and CNI with either MMF or sirolimus. Both univariate analysis and logistic regression were used for determining the association between the genotypes and AR. Univariate analysis detected one significant SNP (p = 0.03), rs1801133, within the methylenetetrahydrofolate reductase (MTHFR) gene associated with AR. Logistic regression analysis identified 2 variants associated with AR, the 32 bp deletion within chemokine (C-C motif) receptor-5 gene (rs333) and the p.222A/V variant (rs1801133) within the MTHFR gene. Though our analysis utilized a much larger cohort than used in previous reports, we were only able to detect an association with 2 of these variants. The lack of validation for the other 19 variants may be due to the small effect size, or that they are not associated with AR. These results stress the need for larger cohorts for both future studies as well as for validation studies.